The Public Understanding of Science. Report of a Royal Society ad hoc Group Endorsed by the Council of the Royal Society - Royal Society, London (England).; Royal Society, London (England). ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
Based on the premise that science and technology directly affect a wide range of personal activities and impact policy issues of national and international importance, this report aims to show why it matters that all sections of the public should have some understanding of science and to stimulate action by scientists and others to improve this understanding. This report resulted from the United Kingdom's Royal Society's recommendation that ways should be investigated to enhance public understanding of science. An introductory statement and a rationale which explains why an understanding of science is important for different groups form the opening chapters in this book. Remaining sections focus on: (1) a review of the state of existing levels of public understanding of science; (2) formal education; (3) mass media; (4) science community; (5) public lectures, children's activities, museums, and libraries; and (6) industry. Conclusions and recommendations are also offered. Appendices contain listings of contributors involved in the preparation of the report. The bibliography consists of sections on surveys, education, science and the media, and sources of a general nature. (ML)
Availability: The Royal Society, 6 Carlton House Terrace, London SW1Y 5AG, England ($10.80).
Practitioners.
Community.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Attitudes; Communications; Community Attitudes; Community Education; Community Role; Industry; Informal Education; Information Dissemination; Museums; School Business Relationship; Science and Society; Science Education; Scientific Literacy; Technology; Public Understanding Of Science Program -- United Kingdom; Opinion Papers; Reports, General